Risk Mitigation in Cold Chain Sytem using ANP and FMEA : A Case Study of PT XYZ - Rohmah, Lailatul; Aryanny, Enny (Advance Sustainable Science Engineering and Technology, 2024)
PT. XYZ is a company that focuses on exporting marine products, especially products for surimi products, PT. XYZ experienced problems in cold chain system activities such as declining quality of fish raw materials, limited cold storage capacity, diversity of supply quality and the risk of overloud storage, resulting in the inhibition of cold chain system activities. The purpose of this study is to identify the causes and provide appropriate mitigation strategies so that risks can be minimized by the Company. This study uses an integration method between ANP and FMEA, so that a WRPN (Weighted Risk Priority Number) value can be produced. Based on the results of the analysis using the integration of the two methods, WRPN was obtained with the highest priority on quality risk factors of 170.713 and storage risk factors of 153.087 so that both risk factors are classified as high risk and need to be mitigated. The mitigation measures provided include separation of contaminated fish, monitoring, microbiological testing, compliance with standards, SOP training, cold storage maintenance, cold storage forecasting, using the FIFO method, supervision of the use of cold storage.